COMPARATION OF INTERNATIONAL COPYRIGHT LAW IN INDONESIA COUNTRIES - HONGKONG - SINGGAPORE - MALAYSIA AND THAILAND VIEWED FROM THE ASPECT OF CRIMINAL SANCTIONS ON CORPORATION - Edi Ribut Harwanto (Muhammadiyah Law Review Journal, 2019)
Copyright Law No. 28 of 2014 concerning Copyright in Indonesia has been ratified since 2014, and came into force and can be implemented or operationalized after two years later in 2016. The main problems that arise with the application of the Copyright Act Cipta in Indonesia there are other issues related to juridical issues regarding the formulation of criminal provisions and related to the problem of unclear issues regarding the formulation of criminal offense qualifications or unclear violations, determination of the subject of corporate law is not regulated, corporate criminal sanctions are not regulated, formulation of sanctions for sanctions that are not clear, against criminal offenses in the Copyright Act. Juridical problems in the Copyright Act in Indonesia will have an impact on the implementation and operation of the current and future Copyright Laws. Furthermore, a discussion on the comparative policy formulation of criminal provisions against corporate legal entities in Indonesia with the Copyright Act in other countries. Copyright Regulations, except for the Indonesian state, do not regulate criminal sanctions against corporations, while Malaysia, Singgapura, Malaysia, Hong Kong and Thailand all regulate criminal sanctions against corporations and include them as strict legal subjects in their material and formal laws. That, proving that, copyright infringement in the eyes of foreign countries is considered important and crucial, so it needs to be regulated in the policy formulation of criminal provisions in that country in order to protect copyright holders, related rights and performers of copyright. Unlike the Copyright Act in Indonesia, only regulates the legal subject of individuals, while corporate legal entities are only referred to in the juridical definition in general provisions of the Copyright Act only, but the provisions in the formulation policy of criminal provisions are not clearly and clearly regulated. Though it is clear that criminal liability sanctions between individuals with criminal sanctions corporate legal entities differ in the imposition of sanctions. Corporations are legal entities created by law. The body that it creates consists of a "corpus" that is, its physical structure and into it the law of entering "animus" which makes the body have a personality. Because the legal entity is a legal creation, except for its creator, its death is also determined by law. To identify how the forms of legal entity are called corporations in general. The corporation has an important characteristic namely; is an artificial legal subject that has a special legal position, has a limited life span, obtains power from the state to carry out certain business activities, owned by shareholders. Shareholder responsibility for corporate losses is usually limited to the shares he owns. Furthermore, to support the objectives of this study, the paradigm used in this study is the post-positivism paradigm. Post-positivism paradigm wants to prove everything is based on reality that can be built based on experience, observation, researchers are neutral towards the object of research, even though researchers holding this paradigm remain neutral towards the object of research, but he wants to examine what actually happens from things that actually as if for sure. The post-positivism paradigm ontologically conceptualizes reality as it really is, but it is realized that there are actually many factors that influence that reality. Consequently, ontologically the post-positivism paradigm conceptualizes the law as a set of rules that apply in society whose behavior will be influenced by economic, political, cultural, and other factors. Epistemologically, researchers sit themselves impersonal, separate from the object of research. The researcher's position on the object of research is neutral and impartial.